2009
DOI: 10.1002/ps.1791
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria‐mediated resistance against the blackeye cowpea mosaic strain of bean common mosaic virus in cowpea (Vigna unguiculata)

Abstract: PGPR strains were effective in protecting cowpea plants against BCMV under both screen-house and field conditions by inducing resistance against the virus. Thus, it is proposed that PGPR strains, particularly GBO3, could be potential inducers against BCMV and growth enhancers in cowpea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Not only biocontrol strains are able to induce plant defence mechanisms against pathogenic attacks, but also PGPR (plant growth promoting rhizobacteria. In this regard, it was shown that strains of Bacillus subtilis and B. pumilus can enhance seed germination of Vigna unguiculata, offering protection against blackeye cowpea mosaic strain of Bean Common Mosaic Virus to the cowpea plants [29]. Similar results were described in tobacco plants treated with PGPR.…”
Section: Induction Of Plant Defensive Mechaniamssupporting
confidence: 64%
“…Not only biocontrol strains are able to induce plant defence mechanisms against pathogenic attacks, but also PGPR (plant growth promoting rhizobacteria. In this regard, it was shown that strains of Bacillus subtilis and B. pumilus can enhance seed germination of Vigna unguiculata, offering protection against blackeye cowpea mosaic strain of Bean Common Mosaic Virus to the cowpea plants [29]. Similar results were described in tobacco plants treated with PGPR.…”
Section: Induction Of Plant Defensive Mechaniamssupporting
confidence: 64%
“…In the case of viruses residing inside the embryo (such as CMV and BCMV), seed treatments with chemicals are often not effective and, in addition, resistance genes are present only in some genotypes. Several studies dealing with seed treatment with Plant Growth-Promoting Bacteria (PGPR) evidenced the PGPR’s effectiveness in improving the health of young plants and, consequently, their resistance to the early viral infections in V. unguiculata [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for plant disease management, the induction of plant resistance by PGPR has become a trend in recent years. Although a large number of studies have focused on PGPR-induced resistance to various bacterial and fungal pathogens (Van Loon et al, 1998;Kloepper et al, 2004), only a few studies have investigated application of PGPR strains for plant viral disease control under greenhouse and/or field conditions (Raupach et al, 1996;DeMeyer et al, 1999;Udaya Shankar et al, 2009;Wang et al, 2009). These studies are mostly associated with bacteria from the genus Bacillus that are in contact with plants to control TMV or CMV via ISR and other mechanisms (Kloepper et al, 2004;Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%